Perbaikan Antarmuka Aplikasi Jurnalisme Positif dengan menerapkan Metode Human Centered Design untuk Pengguna Golongan Tua (Studi Kasus: Times Indonesia) - Atikah Febrianti Nastiti; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Aplikasi Jurnalisme Positif (AJP) is an android mobile application that are used by journalist and general public from age 15 to over 50 years old to write news. As the owner of AJP, Times Indonesia aiming to give people a way to contribute in journalism according to fact in order to decrease the number of negative news through this application. However, there are some difficulty issued by people over age 50, or so called elderly, when they interact with this applications interface. The problems are those users are not able to complete task on some basic feature in this application, they tend to need longer times to finish it and they are not familiar with it. As a result, improvement of the interface to create better design for elderly are needed to increase AJP's usability. In this study, problems related with usability are solved with Human Centered Design (HCD) method. This research evaluates AJP by testing it's effectiveness, efficiency, satisfaction and learnability. The results of the evaluations founds 8 problems and 10 design solution. In addition after applying HCD method and familiarity aspect dimension symbolic and actionable in those design, effectiveness aspect increased from 77% which is below standard to 100%, efficiency aspect from 69,87% successful effective user to 100% and satisfaction aspect increased from 76,75% user satisfied to 91,8% user very satisfied. Learnability aspect are increased along with usability improvements.